How Do Internal Openness and External Openness Affect Innovation Capabilities and Firm Performance? - Wu, Yi-Ching; Lin, Bou-Wen; Chen, Chung-Jen (IEEE transactions on engineering management, 2013)
Open innovation is a paradigm that believes that firms should use both internal and external ideas. These ideas can advance technology and lead to competitive advantage, thereby improving a firm's performance. However, the process of turning innovative ideas into performance does depend on firms' innovation capabilities. In this study, we first divide "openness" into external openness, a search for external channels of information used to innovate, and internal openness, a kind of open culture within a firm. In order to balance value capture with openness, the power of openness in terms of value creation is largely supported by innovation capabilities, including the inherent characteristics of knowledge resources, absorptive capacity, and an entrepreneurial orientation. Our main goals are to state explicitly how a firm's openness strategies influence its innovation capabilities, and explore how to advance innovation capabilities through openness in order to improve performance. Therefore, we use an international and cross-industry survey which was executed by the Managing Innovation in the New Economy (MINE) program. Based on data from 393 firms, our results show that the innovation capabilities of these firms derive from the accumulation of external openness and internal openness. In addition, the findings of this study confirm the role of innovation capabilities in mediating the effect of openness strategies on firms' performance. On the whole, this investigation demonstrates the value of external openness and internal openness to promoting favorable managerial decisions.